2011
DOI: 10.1016/j.renene.2010.10.006
|View full text |Cite
|
Sign up to set email alerts
|

An investigation on renewable energy education at the university level in Turkey

Abstract: In the present study, to discover how teaching of renewable energy sources in Turkey is carried out at the university level, a questionnaire was developed and applied at different universities in Turkey. The analyses conducted on the data obtained from the questionnaire revealed that education about geothermal, solar and wind energy is given at master's level, other renewable energy sources are taught at the undergraduate level within the curriculum of some engineering courses. The teaching performed about ren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 17 publications
1
21
0
5
Order By: Relevance
“…Thus, impacts of renewable energy developments on labour markets should be assessed in the context of not only economic, but also social and environmental contributions, which are sometimes underestimated [23] and [24]. As evidenced by Waclawek et al [25], one of difficult tasks for investors in renewable energy is to find suitable workers with appropriate science and technology skills and engineering knowledge, since boom of this sector creates high demand for highly educated workers like project managers, engineers and operating workers as well [26], [27], [28]and [29]. Such labour demand may cause problems particularly in Central European countries who suffer significant brain drain; free labour movement in the EU draws skilled professionals towards Western Europe where the salaries are much higher.…”
Section: Literature Review; Green Growth and Renewable Energymentioning
confidence: 99%
“…Thus, impacts of renewable energy developments on labour markets should be assessed in the context of not only economic, but also social and environmental contributions, which are sometimes underestimated [23] and [24]. As evidenced by Waclawek et al [25], one of difficult tasks for investors in renewable energy is to find suitable workers with appropriate science and technology skills and engineering knowledge, since boom of this sector creates high demand for highly educated workers like project managers, engineers and operating workers as well [26], [27], [28]and [29]. Such labour demand may cause problems particularly in Central European countries who suffer significant brain drain; free labour movement in the EU draws skilled professionals towards Western Europe where the salaries are much higher.…”
Section: Literature Review; Green Growth and Renewable Energymentioning
confidence: 99%
“…Nevertheless, experience is important, as a perception-based study in the UK showed that a person who has experience in climate change expresses more concern on the probable impacts of changing climate and a willingness to mitigate it by saving energy (Spence et al 2011). A person with proper educational background in the RE sector acquires expertise on it (Karabulut et al 2011), which helps a higher-level perception than that of non-user experts in times of uncertainty (Evar 2011). Qin and Brown (2007) showed that, in a study between two types of participants, a 'consequence'-oriented person demonstrates higher-level judgment than a 'perspective'-oriented one.…”
Section: Discussionmentioning
confidence: 99%
“…According to Karabulut et al [46], fourteen Turkish universities have started Master's and PhD programs in renewable energy, especially in colleges of engineering, focusing on solar, wind, geothermal and hydraulic energy. As of 2011, 73% of the 42 colleges of architecture have core courses about the environment and sustainability.…”
Section: Comparison Of the Standards Used In Leed 2009 Nc And Turkishmentioning
confidence: 99%